Subjective perception of quality of life in nursing students from a public university - Cuellar López, Mayra Vanessa; Montoya Pipicano, Julián Fernando; Castaño Mora, Yamileth (Universidad y Salud, 2016)
Introduction: Education is a factor that influences the quality of life of a person; however, the training process can cause a negative impact on that perception. The great cognitive effort and the requirements derived from the contact with people in condition of sickness and suffering cause stress and anxiety that affect the experience and the quality of life of the nurse in training. Objective: To determine the level of subjective perception of quality of life in nursing students from a public university. Materials and methods: A correlational descriptive study was performed with 112 active nursing students during the period of August and December, 2014. The sociodemographic data survey and the GENCAT Scale of Quality of Life were used. Results: The average index of subjective perception of quality of life was 106, which shows good appreciation of the current life condition. The best assessed dimension was Rights with 87.1% and the one with the lowest score was Physical well-being with 77.3 %. The student considers of greatest impact and importance the accompaniment, emotional and spiritual support from a solid support network throughout the course of his or her training period over the financial stability or the material acquisition capacity he or she can have.